Viscous energy loss in the presence of abnormal aortic flow. Issue 3 (2nd October 2013) - Barker, Alex J.; van Ooij, Pim; Bandi, Krishna; Garcia, Julio; Albaghdadi, Mazen; McCarthy, Patrick; Bonow, Robert O.; Carr, James; Collins, Jeremy; Malaisrie, S. Chris; Markl, Michael
<x xml:space="preserve">Abstract</x> Purpose To present a theoretical basis for noninvasively characterizing in vivo fluid‐mechanical energy losses and to apply it in a pilot study of patients known to express abnormal aortic flow patterns. Methods Four‐dimensional flow MRI was used to characterize laminar viscous energy losses in the aorta of normal controls (n = 12, age = 37 ± 10 yr), patients with aortic dilation (n = 16, age = 52 ± 8 yr), and patients with aortic valve stenosis matched for age and aortic size (n = 14, age = 46 ± 15 yr), using a relationship between the three‐dimensional velocity field and viscous energy dissipation. Results Viscous energy loss was elevated significantly in the thoracic aorta in patients with dilated aorta (3.6 ± 1.3 mW, P = 0.024) and patients with aortic stenosis (14.3 ± 8.2 mW, P < 0.001) compared with healthy volunteers (2.3 ± 0.9 mW). The same pattern of significant differences was seen in the ascending aorta, where viscous energy losses in patients with dilated aortas (2.2 ± 1.1 mW, P = 0.021) and patients with aortic stenosis (10.9 ± 6.8 mW, P < 0.001) were elevated compared with healthy volunteers (1.2 ± 0.6 mW). Conclusion This technique provides a capability to quantify the contribution of abnormal laminar blood flow to increased ventricular afterload. In this pilot study, viscous energy loss in patient cohorts was significantly elevated and indicates that cardiac afterload is increased due to abnormal flow. Magn Reson Med 72:620–628, 2014. © 2013 Wiley Periodicals, Inc.